State of accreditation of undergraduate dental programs in Chile, 2015 - Anggelo Carrizo (Universidad de Concepción., 2016)
Aim: To describe the accreditation of undergraduate dental programs in Chile according to the 2015 assessment procedures of the National Accreditation Commission. Methodology: Descriptive study. The unit of analysis are the resolutions on accreditation of dental programs in Chile by the National Accreditation Commission (CNA-Chile), accessed from the advanced search engine at the CNA-Chile website. From the resolutions the following information was obtained: Effective date, Years of accreditation, Accrediting agency and the Strengths and Weaknesses of the 3 dimensions assessed in undergraduate programs: Graduate profile and results, Operating conditions and Self-regulation. Universities that belonged to the Council of Rectors of Chilean Universities (CRUCH) and to the Chilean Association for Dental Education (ACHEO) were considered in the study. Results: Fourteen universities have a history of accreditation of dental programs. They all belong to ACHEO and half of them are members of CRUCH. The range of accreditation was 2-7 years. The average years of accreditation in private universities was 4.57±1.72, while in CRUCH it was 6±1, with an overall average of 5.29±1.54. The programs have been accredited by CNA-Chile and 4 other accrediting agencies. Conclusion: There is significant variability in the quality of dental programs in Chile according to CNA-Chile accreditations. Programs from CRUCH universities have a better and more consistent quality than those of private institutions.